Effect of Magnetic Elements Substitution on the Intergranular Properties of Bi-Based Superconductors - Adam, Malik Idries (2003)
The effects of magnetic elements substitution for calcium position in the Bi₁.₆Pb₀.₄Sr₂(Ca₁₋ₓMₓ)Cu₃Oδ with M=Pr, Nd, Sm, Gd, Dy or Ni and x=0.0- 0.10 system , prepared by the conventional solid state reaction method have been investigated by means of structural , transport and magnetic methods. The samples were sintered in air at 855°C for 150 hours followed by annealing at 830°C for 30 hours. The superconducting properties such as volume fraction of present phases, lattice parameters, grain shape and critical temperatures were affected by the introduction of different elements for Ca in the system. The volume fraction of the high-Te{2223} phase decreases and that of the low-Te(2212) phase increases with the increase of osubstituents. As a result, the c-axis parameter decreased from 37 A to o 30.7 A at initial substitution stages for all samples. Thus, the critical temperature, Te decreased to that of the low-Tc(2212) phase. The morphological aspects of the samples generally show platelet-like grains with random orientations, typically for 2212 and 2223 phase's structure. Air annealing at 830°C for 30 hours slightly improved the physical properties of the samples.